EFFECT OF TRAINING AND AFFECTIVE COMMITMENT ON EMPLOYEE PERFORMANCE THROUGH SELF EFFICACY AS INTERVENING VARIABLE (STUDY AT PT. TELEKOMUNIKASI INDONESIA TBK WITEL SEMARANG) - Hikmah El Maula; Intan Ratnawati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The purpose of this study was to analyze and obtain evidence of the effect of training and affective commitment on employee performance through self-efficacy as an intervening variable (study on employees of PT. Telekomunikasi Indonesia Tbk Witel Semarang). The population of this study were all permanent employees of PT. Telekomunikasi Indonesia Tbk Witel Semarang and sampling using the saturated technique or the census technique amounted to 120 samples. Collecting data using a questionnaire with the criteria that the respondent has become a permanent employee. The data processing and analysis uses SEM modeling equations with the AMOS program. The results of this study indicate that training has a positive and significant effect on employee performance, affective commitment has no and significant effect on employee performance, training has a positive and significant effect on self-efficacy, affective commitment has a significant and positive effect on self-efficacy, and self-efficacy has an effect on employee performance. Keywords Training; Affective Commitment; Self Efficacy; Employee performance